Comparison of dietary inclusion of commercial and fermented soybean meal on oxidative status and non-specific immune responses in white shrimp, Litopenaeus vannamei. Issue 63 (April 2017) - Lin, Yu-Hung; Mui, Jia-Jinn
Abstract: This study compared the effects of partial replacement of fish meal (FM) protein with commercial soybean meal (SBM) or Lactobacillus spp. fermented SBM (FSBM) on the oxidative status and non-specific immune responses in white shrimps, Litopenaeus vannamei . A FM-based diet was used as the control. To prepare the two experimental diets, 25% of the FM protein was replaced with SBM and FSBM. Three experimental diets were fed to three groups of shrimps (initial wt: 0.63 ± 0.01 g) in a recirculating rearing system for 12 weeks. The SBM-diet group had the highest hepatopancreatic thiobarbituric acid-reactive substance value, followed by the FSBM-diet group, and the lowest in control-diet group. The activity of hepatopancreatic superoxide dismutase was highest in the control-diet group, followed by the FSBM-diet group, and was lowest in the SBM-diet group. The total haemocyte, hyaline cell, semigranular cell, and granular cell counts were highest in the control-diet group, followed by the FSBM-diet group and the SBM-fed group. Haemolymph phenoloxidase activity was higher in the control-diet and FSBM-diet groups than in the SBM-diet group. The results indicate that replacing 25% FM protein with SBM significantly reduces non-specific immune responses and induces oxidative stress in white shrimps and that FSBM prepared using Lactobacillus spp. can reduce these negative effects. Highlights: Soybean meal (SBM) in diet induces high oxidative status of white shrimp. SBM in diet also reduces immune responses of white shrimp. SBM prepared using Lactobacillus spp. can improve the negative effects for shrimp.